Pengaruh Transparent Communication dan Communicated Appreciation Terhadap Job Engagement yang Dimediasi oleh Affective Organizational Commitment pada Karyawan RSGM-P FKG Usakti - Kresentia Keisha; Andreas Wahyu Gunawan P (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study aims to analyze the effect of transparent communication and communicated appreciation on job engagement mediated by affective organizational commitment to the employees of RSGM-P FKG Usakti. This study uses a quantitative method that uses primary data sourced from questionnaires distributed via google forms to employees at RSGM-P FKG Usakti. The research sample was selected using the entire population of 210 employees, consisting of medical and non-medical personnel at RSGM-P FKG Usakti. Analysis of the data used for the hypothesis is Covariance-Based Structural Equation Modeling (CB-SEM), the software used is AMOS, and to test the hypothesis of the mediating variable using the Sobel Test. The results of this study indicate that there are several hypotheses that have a positive effect, including; transparent communication on job engagement; communicated appreciation on job engagement; transparent communication on affective organizational commitment; and communicated appreciation on affective organizational commitment. In addition, the results of this study also found information that there was no positive influence between affective organizational commitment on job engagement; transparent communication on job engagement through affective organizational commitment; and communicated appreciation on job engagement through affective organizational commitment. This research is expected to be a reference for further research on respondents in other health fields or outside the health sector, as well as further research on other factors outside of this research that may influence or mediate job engagement